The Need For Participation In Open And Distance Education: The Open University Malaysia Experience - Santhi, Raghvan; Rajesh Kumar, P. (2007)
This paper provides an overview of adult learner participation in open and distance education by focusing participation needs based on selected socio-demographic variables such as age, years of working experience and monthly income. The related study involved a sample of 454 Open University Malaysia students from a number of learning centres located in different parts of the country. The study found that adult learners are generally below the age of 39, relatively not affluent, have less than 20 years of work experience and have a high need for participation. The highest need is professional advancement, followed closely by cognitive interest, and communication improvement while the lowest reported need is escapism/social stimulation. Age and work experience exhibited negative regression coefficients, indicating inverse associations with participation need. These results are comparable to the findings of previous research on the role of age, work experience and monthly income as factors determining participation in adult higher education.